Sulforaphane decreases kidney injury after transplantation in rats: role of mitochondrial damage - Cekauskas, Albertas; Bruns, Helge; Manikas, Martynas; Herr, Ingrid; Groß-Weissmann, Marie-Luise; Zorn, Markus; Jankevicius, Feliksas; Strupas, Kestutis; Schemmer, Peter (Annals of transplantation, 2013)
BACKGROUND: Sulforaphane is a naturally occuring antioxidative and anti-inflammatory isothiocyanat. In this study, its impact on experimental kidney transplantation was evaluated. - MATERIAL AND METHODS: Male Brown Norway rats (n=112) were used as experimental animals. Donor kidneys were harvested and stored for 12 hours in HTK-solution at 4°C. D,L-Sulforaphane (4.4 mg/kg BW; 0.2ml) or normal saline (0.2 ml) was given i.v. to the recipients 24 and 1 hour before, and 6 hours after transplantation. Recipients were nephrectomized bilaterally and subsequently transplantation was performed. After 6 and 48 hours, biopsies were taken and processed for light and electron microscopy. Graft function was monitored using serum values of creatinine and BUN after 6 and 24 hours. Quantitative real-time PCR was used to detect differences in SOD2-gene expression after 6 hours and apoptotic activity was detected after 6 hours using propidium iodide flow cytometry. - RESULTS: Recipient preconditioning improved reperfusion damage index from 12.8±1.6 in controls to 8.8±1.8 (p<0.001). Serum levels of creatinine and BUN decreased from 4.29±0.25 mg/dl and 119±23 mg/dl in controls to 3.65±0.7 mg/dl and 81±19 mg/dl (p<0.05). The number of severely injured tubules decreased (p<0.05). Apoptotic activity was increased in SFN-treated rats. Mitochondrial microstructure was better preserved after SFN, while SOD 2 gene expression increased (p<0.05). - CONCLUSIONS: SFN ameliorates ischemia/reperfusion injury after KTx, most likely through anti-oxidative effects.
Gesehen am 18.03.2021